MIGRATION OF PENJA (AMPHIDROMOUS GOBY) - Nurjirana, Nurjirana -; Burhanuddin, Andi Iqbal; Haris, Abdul - (Jurnal Penelitian Perikanan Indonesia, 2023)
Penja fish belong to the group of goby fish that migrate amphidromously and consist of various species with varying migration periods. In their life cycle, some species experience changes in shape (metamorphosis) and changes in body color caused by changes in habitat and eating habits, namely from planktivore when they are at sea turning into herbivore and becoming benthic organisms when in rivers. The time period of penja fish migration has a correlation with the occurrence of a new moon phase accompanied by rain. The silting of the river and development in the river area without a fish migration route will cut off the migration path for the amphidromous goby species, in addition, the phenomenon of drought in every dry season also threatens the existence of freshwater ichthyofauna.